The effect of densification on hardness of Ti, Ti-6Al-4V, Ti-34Nb-25Zr alloy produced by spark plasma sintering. (2021) - Mahundla, M.R.; Matizamhuka, W.R.; Shongwe, M.B.
Abstract: Titanium alloys are often used owing to their superior mechanical properties such as hardness. The sintered samples of Ti, Ti-6Al-4V (Ti-64) and Ti-34Nb-25Zr (TNZ) were produced through powder metallurgy route comprising of mechanical alloying and spark plasma sintering. The samples were mechanically alloyed at 500 rpm and sintered at 1200 °C, heating rate of 100 °C/min, pressure of 50 MPa and holding time of 10 min. The sintered samples were characterized for densification and Vickers microhardness values of Ti, Ti-64 and TNZ were 371.41, 385.48 and 590.22 HV at 0.5 kg load, respectively. Densification values were between 97 and 100%. Hardness of a material is directly affected by its densification.